Childhood adversities and prior involvement with child protective services - Shakira F. Suglia; Erin R. Kulick; Jocelyn Brown (BMC, 2019)
Abstract Objectives We aimed to determine the relation between childhood adversities and prior involvement with Child Protective Services (CPS) history among children presenting for evaluation at a Child Advocacy Center. Study design The study evaluated children presenting to a Child Advocacy Center (CAC) from 2009 to 2014. A five-item child adversity measure, based on mother's report, was characterized into a scale of none, one, or two or more adversities. Caseworkers at the CAC assessed whether families had a prior history of involvement with CPS. Results Among the 727 children included in the analyses, 43% had a prior history of involvement with CPS. Twenty-six percent of the children experienced one childhood adversity while 29% experienced two or more. In regression analyses adjusting for socio-demographics, experiencing one (Prevalence Ratio (PR) 1.25 95%CI 1.0-1.5) or two or more adversities (PR1.67 95%CI 1.4, 2.0) was associated with higher prevalence of CPS history compared to those who reported none. Conclusions Childhood adversities are associated with prior contact with CPS, suggesting there are missed opportunities to provide services to high-risk families. CACs may be in a unique position to advocate for families and prevent further victimization of children.